Shrine dedicated to Kwan Kung - Mumbai Archive Project Team (Jio Institute, 2024)
The shrine on the first floor is dedicated to Kwan Kung. He is venerated as a God of war, righteousness, and loyalty in various Chinese religious traditions, including Confucianism, Taoism, and Chinese folk religion. Revered for his martial valour and ability to protect against evil spirits, Kwan Kung is typically depicted with a red face, a long beard, and wearing traditional Chinese armour.